Mycotoxigenic fungi and mycotoxins contaminating red rice at consumer level in Selangor, Malaysia / Nik Iskandar Putra Samsudin - Nik Iskandar Putra, Samsudin (2011)
Red rice is a product of rice fermentation by fungi from the genus Monascus notably the M. purpureus, M. ruber, and M. pilosus. Although the traditional method of its preparation does not necessarily adhere to safety and health regulation, it is still widely consumed by Chinese as traditional herbal remedy believed to possess outstanding and diverse industrial, clinical, and food applications. The present study was undertaken to determine the occurrence of mycotoxigenic fungi and mycotoxins present on red rice at consumer level in Selangor, Malaysia. In this study, 50 samples of red rice were obtained from nine administrative districts of the state Selangor. Twenty nine were stored at cold temperature (refrigeration) and 21 at room temperature. For fungal isolation and enumeration, samples were plated on Dichloran Rose Bengal Chloramphenicol (DRBC) and Czapek Dox (CD) agars by direct- and dilution-plating techniques. Identification of fungi was done morphologically (micro and macro) according to published manuals. There was no significant difference (p 0.05) in Colony Forming Unit (CFU) readings between cold and room temperatures with the highest being 2.1 x 106 CFU/g and the lowest 1.4 x 104 CFU/g. The readings were above the permissible limit set by Malaysian Ministry of Health of not more than 102 CFU/g, and International Commission for Microbiological Specification of Foods of 102 to 105 CFU/g. Besides the starter fungi Monascus spp. which were present in 50 samples (100%), three other species were also found to be predominant namely, Penicillium chrysogenum (62%), Aspergillus niger (54%), and Aspergillus flavus (44%) which were classified as potent mycotoxigenic fungi in foods and feedstuffs. Mycotoxins were determined by enzyme-linked immunosorbent assay (ELISA). Citrinin, aflatoxin, and ochratoxin-A were evaluated based on the presence of producer fungi in the samples. Citrinin was present in 50 samples (100%) at 229.50 to 20,648.75 ppb. Aflatoxin was present in 46 samples (92%) at 0.61 to 77.33 ppb. Ochratoxin-A was present in 50 samples (100%) at 0.23 to 2.48 ppb. A hundred per cent citrinin (50/50), 76.09% aflatoxin (35/46), and 0% ochratoxin-A (0/50) were present critically above the permissible limit set by Malaysian Ministry of Health of not more than 5 ppb of all mycotoxins in food, and European Union at 4 ppb for aflatoxin, and 3 ppb for ochratoxin in food. There is a slight but insignificant (p 0.05) correlation between presence of mycotoxigenic fungi and mycotoxins as the presence of fungal contaminants cannot ultimately ascertain the presence of mycotoxins. Presence of fungal contaminants only served as an initial indicator of possibility of mycotoxins contamination. In conclusion, all red rice samples were contaminated with mycotoxigenic fungi and mycotoxins above the permissible limits for human consumption. This in turn might indicate improper production, handling, transportation, and storage practice of the commodity. It is henceforth suggested that traditional production of red rice should adhere to scientific inspection and clinical regulation, and toxicity studies on the nephrotoxic effect of citrinin produced by the starter fungi in red rice should be carried out to confirm the safety and health status of red rice.